Rancang Aplikasi Pendaftaran Siswa Baru Berbasis Website : (Studi Kasus SMP MIFTAHURROHMAN) - Wafiq Azizah; Umi Chotijah (STIKes Ibnu Sina Ajibarang, 2024)
The new student enrollment process at SMP MIFTAHURROHMAN faces various challenges in terms of efficiency and effectiveness. The current manual process often leads to delays and errors, and fails to meet enrollment targets. To address these issues, we developed a web-based application designed to facilitate the enrollment of new students. This application allows students to register online, upload supporting documents, and print registration receipts. The system is built using the waterfall method and technologies such as PHP, MySQL, and the CodeIgniter framework. Both students and school administrators can monitor and manage registration data in real-time. The implementation of this application is expected to make the new student enrollment process faster, more accurate, and transparent, thereby improving operational efficiency and user satisfaction. This research shows that the developed application effectively addresses the existing problems and provides significant benefits for the school.